A P7 Phage-Like Plasmid Carrying mcr-1 in an ST15 Klebsiella pneumoniae Clinical Isolate - Zhou, Weilong; Liu, Lu; Feng, Yu; Zong, Zhiyong (Frontiers in Microbiology, 2018)
A Klebsiella pneumoniae clinical strain, SCKP83, was resistant to colistin and had the plasmid-borne colistin resistant gene mcr-1. The strain was subjected to whole genome sequencing and conjugation experiments. It belonged to ST15 and the capsular type K41. In SCKP83, mcr-1 was carried by a 97.4-kb non-self-transmissible plasmid, a 90.9-kb region of which was predicted as an intact phage. This phage was 47.79% GC content, encoded 105 proteins and contained three tRNAs. mcr-1 was located downstream of two copies of the insertion sequence ISApl1 (one complete and one truncated) and was inserted in the ant1 gene, which encodes a putative antirepressor for antagonizing C1 repression, in this phage. The phage is highly similar to phage P7 (77% coverage and 98% identity) from Escherichia coli. Several similar mcr-1-carrying plasmids have been found in E. coli at various locations in China, suggesting that these phage-like plasmids have circulated in China. The findings in this study suggest that the P7 phage-like plasmids are not restricted to E. coli and may represent new vehicles to mediate the inter-species spread of mcr-1.